2012
DOI: 10.1021/om300830n
|View full text |Cite
|
Sign up to set email alerts
|

Organocopper Compounds: From Elusive to Isolable Species, from Early Supramolecular Chemistry with RCuI Building Blocks to Mononuclear R2–nCuII and R3–mCuIII Compounds. A Personal View

Abstract: The first reports on copper-mediated organic reactions and speculations about the role of presumed organocopper compounds as intermediates or transient species date back to the early 20th century. Since that time, copper salt mediated and much later, copper-catalyzed C−X bond forming reactions (X = C, O, N) have been developed. Phenyl-and methylcopper(I) (highly explosive as a dry solid) were the first organocopper materials synthesized by Reich (1923) and Gilman (1952), respectively. However, it was not unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 120 publications
(193 reference statements)
3
35
0
Order By: Relevance
“…Initially, the impurity of the synthesized organocopper(I) material created a major problem which hampered their testing as biocides. Careful study of this phenomenon showed, however, that not only RCu aggregates undergo interaggregate exchange but that also, and sometime with high selectivity, R'Cu and CuX (and MX in general) species can become involved to the effect that thermodynamically stable hetero aggregate species can be formed and isolated in almost quantitative yield; an example of this is Cu 6 Br 2 (C 6 H 4 NMe 2 -2) 4 2 [3]. In this case, the heteroaggregate is more stable than the homoaggregate Cu n (C 6 H 4 NMe 2 -2) n to the effect that isolation of the pure organocopper (from the reaction of Li(C 6 H 4 NMe 2 -2) with CuBr in Et 2 O) is impossible.…”
Section: Organo-copper and -Lithium Chemistry [1e5]mentioning
confidence: 99%
See 3 more Smart Citations
“…Initially, the impurity of the synthesized organocopper(I) material created a major problem which hampered their testing as biocides. Careful study of this phenomenon showed, however, that not only RCu aggregates undergo interaggregate exchange but that also, and sometime with high selectivity, R'Cu and CuX (and MX in general) species can become involved to the effect that thermodynamically stable hetero aggregate species can be formed and isolated in almost quantitative yield; an example of this is Cu 6 Br 2 (C 6 H 4 NMe 2 -2) 4 2 [3]. In this case, the heteroaggregate is more stable than the homoaggregate Cu n (C 6 H 4 NMe 2 -2) n to the effect that isolation of the pure organocopper (from the reaction of Li(C 6 H 4 NMe 2 -2) with CuBr in Et 2 O) is impossible.…”
Section: Organo-copper and -Lithium Chemistry [1e5]mentioning
confidence: 99%
“…2. Structures of 1 Cu 4 (C 6 H 3 CH 2 NMe 2 -2-Me-4) 4 [6] and 3 Cu 2 Li 2 (C 6 H 4 CH 2 NMe 2 -2) 4 [7]. (Reproduced with permission from ref 3; copyright Wiley-VCH Verlag GmbH & Co.…”
Section: Organo-copper and -Lithium Chemistry [1e5]mentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Some experimental evidences of formation of adducts between copper complexes and organic radicals were obtained, [4][5][6][7][8][9][10][11][12][13][14] but the information on their structure was very scarce. Over the last years organometallic chemistry of Cu(I) and Cu(III) was vastly in progress [15,16] in contrast to Cu(II); only few stable organocuprates (II) are known to date. [17][18][19][20][21][22][23][24] Meanwhile, due to spectral data not a few labile transients, probably compounds with Cu(II)AC bond, may form in conditions of catalytic and photochemical reactions or directly by reaction of Cu(I) complexes with organic radicals.…”
Section: Introductionmentioning
confidence: 99%